SISI KENUSANTARAAN DALAM KITAB KITAB AL-TAFSĪR AL-IKLῙL FῙ MAᾹNI AL-TANZῙL KARYA KH. MISBAH MUSTHAFA - Siti Aisyah (AL ITQAN: Jurnal Studi Al-Qur'an, 2019)
The Nusantara side (Nusantara aspect) is found in the interpretation of KH Miṣbah Muṣṭhafa in the al-Iklīl Fī Maanī al-Tanzīl which was written in 1977 and completed in 1985 in Bangilan, Tuban. Therefore, this study is focused on how KH Miṣbah Muṣṭhafa interpreted the verses of the al-Qur`an according to the conditions in the surrounding environment at that time. This research uses descriptive-analytical method with Gadamer's hermeneutics approach to reveal the Nusantara aspect of the book. Through the horizon of the reader (mufassir), then the meaning is sought in accordance with the author's intent (al-Qur`an) so that the meaning of the verse of al-Qur`an becomes objective. This study reveals that KH Miṣbah Muṣṭhafa in interpreting the verses of al-Qur`an uses asbab al-nuzul first, then interpreted the verse according to the condition of the surrounding environment by paying attention to the undak usuk ( Javanese hierarchical language), either using Javanese Krama Inggil, Krama Lugu, or Ngoko (high, middle and low level of Javanese language). KH Miṣbah Muṣṭhafa also responded to the existing problems by prohibiting the use of loudspeakers in mosques, family planning (KB) and bank interest because according to him they were categorized as heresy.